3D steady-state diffusion-weighted imaging with trajectory using radially batched internal navigator echoes (TURBINE). - McNab, J; Gallichan, D; Miller, K (2010)
While most diffusion-weighted imaging (DWI) is acquired using single-shot diffusion-weighted spin-echo echo-planar imaging, steady-state DWI is an alternative method with the potential to achieve higher-resolution images with less distortion. Steady-state DWI is, however, best suited to a segmented three-dimensional acquisition and thus requires three-dimensional navigation to fully correct for motion artifacts. In this paper, a method for three-dimensional motion-corrected steady-state DWI is presented. The method uses a unique acquisition and reconstruction scheme named trajectory using radially batched internal navigator echoes (TURBINE). Steady-state DWI with TURBINE uses slab-selection and a short echo-planar imaging (EPI) readout each pulse repetition time. Successive EPI readouts are rotated about the phase-encode axis. For image reconstruction, batches of cardiac-synchronized readouts are used to form three-dimensional navigators from a fully sampled central k-space cylinder. In vivo steady-state DWI with TURBINE is demonstrated in human brain. Motion artifacts are corrected using refocusing reconstruction and TURBINE images prove less distorted compared to two-dimensional single-shot diffusion-weighted-spin-EPI.